Clogging and flow characteristics of a geosynthetic drain confined in soils undergoing consolidation. Issue 1 (February 2004) - Ghosh, C.; Yasuhara, K.
Abstract : This paper describes clogging and in-plane flow characteristics of a permeable geosynthetic layer confined within fine-grained soils that undergo time-dependent settlement. The drain layer was placed within a slurry, and measurement of water from the drain layer was recorded. In-plane flow capacity of the drain layer was checked at the end of consolidation. The permeability of the geosynthetic drain layer was found to be at least 10 5 times the corresponding permeability of the soil. In order to prevent clogging, a hybrid drain system consisting of a thin sand mat between the soil and geosynthetic layer was investigated. This system showed excellent drainage performance due to good filtering capability of the thin sand mat. New terms, such as 'permeability factor', 'drain performance factor', 'confining pressure factor' and 'clogging potential' of drain, are defined and evaluated from the experimental data. Clogging potential of the hybrid drain layer was found to be low (< 2), and was observed to reduce with an increase in consolidation pressure. Without the thin sand mat the clogging potential showed an increasing trend with increasing consolidation pressure. Finally, this paper recommends potential application of the hybrid drain system to improve stability of soil structures constructed with poorly draining backfills such as Kanto loam in Japan.